Governance structure of microfinance institutions: A comparison of models and its implication on social impact and poverty reduction - Uddin, Md Nazim; Hamdan, Hamdino; Che Embi, Nor Azizan; Kassim, Salina; Md Saad, Norma (2019)
The purpose of this paper is to compare three different models of MFIs, namely microfinance banks (MFB), Microcredit programme (MCP) and rural development scheme (RDS), by focusing on their governance structures, and subsequently analyse their implications on social impact and poverty reduction of the MFIs. Three MFIs, one from each model, will be considered, using Bangladesh as the case study. Bangladesh is a country which is considered to be a pioneer in providing micro-finance to the underprivileged people to improve their entrepreneurial capacity. The objective of this study, to determine the relationship between governance structure with social impact and poverty reduction of microfinance institutions (MFIs). In methodology, the study relies on Porter’s Competitive Strategy Theory (1979). This theory is based on the concept that five forces determine the competitive intensity and attractiveness of a market which assesses five forces. Determine the attractiveness of a business entity and affect its ability to serve its customers and make a profit. The study relies on secondary data collected mainly from the annual reports of the three MFIs, and Microcredit Regulatory Authority (MRA) report. This study aims to contribute towards better governance practices of the MFIs given its strong implications on social responsibility, accountability, transparency, financial performance, increasing their social impact and poverty reduction of the MFIs. Findings of this study provide essential inputs on the way forward for the evolution of microfinance, as framed by the global development discourse and subsequent public policy choices. Overall, the study shows that only a limited number of variables influence the social impact and poverty reduction of an MFI. The limitation of the studied investment fund is that it invests in expanding and mature MFI’s. So the results of this research can only be generalised to expanding and mature MFI’s. The governance structure was recommended in the industry guidelines and which are studied here are often not relevant concerning the social impact and poverty reductions of MFIs. The approach to microfinance governance should be broadened by focusing more on stakeholders and the decision making process in an MFI. Better social responsibility and poverty reduction of the MFIs contribute positively to financial inclusion through poverty alleviation, empowerment of the poor and better financial access, leading to sustainable economic growth.